2023
DOI: 10.3390/su15032562
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Entrepreneurship Education on Entrepreneurial Intention: Mediation of Entrepreneurial Self-Efficacy and Moderating Model of Psychological Capital

Abstract: Based on planned behavior theory (TPB), this study aims to explore the direct or indirect impacts of entrepreneurship education on entrepreneurial intentions through entrepreneurial self-efficacy and explore the moderating role of psychological capital. Sample data were collected by sending online electronic questionnaires to university students in some universities in Guangxi. A structural equation model was used to test the 757 valid sample data. The results showed that: (1) college students of different gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 105 publications
1
13
0
4
Order By: Relevance
“…Similarly, a study by Aliedan et al [9] employing structural equation modelling (SEM) as the main data analysis technique found that university education support and subjective norms (external factors), personal attitude, and perceived behavior control (internal factors) are significant predictors of green entrepreneurship intentions among 390 students in Kingdom of Saudi Arabia (KSA). Additionally, using a SEM data analysis method, Wang et al [10] found that other different factors such as entrepreneurial self-efficacy optimism (internal factors), ecological values, and social responsibility (external factors) have a positive impact on green entrepreneurship intentions among 410 Chinese college students. On the other hand, using multiple linear regression analysis techniques, Aditya [11] found that university education failed to positively impact entrepreneurship intentions among 95 students at Jakarta State University, Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a study by Aliedan et al [9] employing structural equation modelling (SEM) as the main data analysis technique found that university education support and subjective norms (external factors), personal attitude, and perceived behavior control (internal factors) are significant predictors of green entrepreneurship intentions among 390 students in Kingdom of Saudi Arabia (KSA). Additionally, using a SEM data analysis method, Wang et al [10] found that other different factors such as entrepreneurial self-efficacy optimism (internal factors), ecological values, and social responsibility (external factors) have a positive impact on green entrepreneurship intentions among 410 Chinese college students. On the other hand, using multiple linear regression analysis techniques, Aditya [11] found that university education failed to positively impact entrepreneurship intentions among 95 students at Jakarta State University, Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding Hypothesis 3, the findings show that an entrepreneurial self-efficiency had a positive and significant influence on the students’ intention to engage in entrepreneurial activity. People with higher levels of self-efficacy have greater intents, and they also believe that they are more likely to accomplish positive outcomes by tracking a decided plan ( Wang et al, 2023 ). This was discovered in studies that examined the direct impact of self-efficacy on entrepreneurial ambitions.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing the direct effect of entrepreneurship education and students' interests in social entrepreneurship, the indirect effects of self-efficacy are even more prominent; this highlights the role of self-efficacy in cultivating entrepreneurial intention amongst students. As shown by Wang et al (2023), selfefficacy has an important mediating role, one that -due to the importance of psychological capital -is frequently determinant in the emergence of social entrepreneurial intention.…”
Section: Self-efficacymentioning
confidence: 99%
“…The measuring instrument for the role model (RM) variable was developed based on earlier studies by Amofah and Saladrigues (2022), Chereau and Meschi (2022), and Boldureanu et al (2020). Self-efficacy was measured using items from Urban (2020), Pan and Lu (2022), and Wang et al (2023). Attitude toward social entrepreneurship was measured using items adapted from Amofah and Saladrigues (2022) and Sancho et al (2020).…”
Section: Measurementioning
confidence: 99%